Aplicación móvil para la toma de pedidos a domicilio en la Pizzería "Buongiorno" - Terán Panchi, Alex Gustavo (2017)
This project is focused on eradicating the problem in the "Buongiorno" pizzeria located in Latacunga city from Cotopaxi Province. The difficult is when home orders are requested. The pizzeria doesn’t have the appropriate technology to automate this process; it has caused economic loss for its owners. The company has seen viable the implementation of a technological solution for this problem, considering that the automation of processes and the management of data, allows generating and analyzing information for decision-making. For the development of the mobile application were applied tools like Android Studio, in order to optimize the control delivery times of the final product. Deductive method was applied in the research development through the use of techniques such as interviews, surveys and observation, on the basis of which the real problem was understood and analyzed. In the development of this project, the Mobile-D methodology was used for the mobile application, since it allows fast results and is characterized by working in small groups and for the web application of the administrator the SCRUM methodology due to it allows a greater communication between the customer and the development team, thus allowing greater productivity and quality of the final product. With the implementation of the mobile application "Buongiorno" pizzeria has been benefitted at the moment of receiving the orders made by the users, as the process was automated and carried out with fluidity and efficiency, resulting in an innovative service to the final customer and the display of products in the administrator's system.